Chirurgische Therapie im Stadium I und II des nichtkleinzelligen Lungenkarzinoms - Klotz, Laura Valentina; Winter, Hauke (Der Onkologe, 2018)
Despite modern diagnostics and multimodal treatment strategies, overall survival of lung cancer could not be significantly improved in recent decades. The majority of patients with non-small cell lung cancer (NSCLC) have distant metastases at the time of diagnosis (57%) and only approximately 40% of patients are in a potentially curable tumor stage.
Gesehen am 18.11.2019